Depth heterogeneity of lignin-degrading microbiome and organic carbon processing in mangrove sediments - Jijuan Ding; Fei Liu; Jiaxiong Zeng; Hang Gu; Jing Huang; Bo Wu; Longfei Shu; Qingyun Yan; Zhili He; Cheng Wang (npj Biofilms and Microbiomes)
Abstract Mangrove ecosystems are globally recognized for their blue carbon (C) sequestration capacity. Lignocellulosic detritus constitutes the primary C input to mangrove sediments, but the microbial processes involved in its bioprocessing remain unclear. Using lignocellulosic analysis and metagenomic sequencing across five 100-cm sediment cores, we found a high proportion of lignin (95.0–97.7%) within sediments’ lignocellulosic detritus, with a small fraction of lignin-degrading genes (1.24–1.98%) of lignin-degrading genes within the carbohydrate-active enzyme coding genes. Depth stratification was observed in genes and microbial communities involved in lignin depolymerization and mineralization of lignin monomer derivatives. Further microbe-centered analyses of biomass production rates and adaptive metabolism revealed diminished microbial C use efficiency potential and augmented “enzyme latch” with increasing sediment depths. These findings enhance our understanding of sedimentary organic C cycling and storage in coastal blue C ecosystems.